1989
DOI: 10.1002/app.1989.070380404
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical properties of UV‐cured urethane films

Abstract: SynopsisA series of novel photosensitive urethane oligomers was synthesized in which methacryloyl group was contained in the hard segment. The hard segment was prepared by reacting 4,4'-diphenylmethane diisocyanate with glycerine mono methacrylate, which was successively reacted with three kinds of glycols involving l,4-poly(butadiene glycol), poly(propy1ene glycol), and poly(capro1actone diol). The mechanical properties of synthesized urethane oligomers after irradiating with ultraviolet light were evaluated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

1993
1993
2008
2008

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 3 publications
0
6
0
Order By: Relevance
“…It has been also reported that the degree of microphase separation in crosslinked urethane acrylate films strongly influences the mechanical properties of its film 15,36–38. As the degree of microphase separation between hydrophilic and hydrophobic or between soft and hard segments increases, tensile strength, elongation, and glass transition temperature of crosslinked polyurethane films increases.…”
Section: Resultsmentioning
confidence: 98%
See 1 more Smart Citation
“…It has been also reported that the degree of microphase separation in crosslinked urethane acrylate films strongly influences the mechanical properties of its film 15,36–38. As the degree of microphase separation between hydrophilic and hydrophobic or between soft and hard segments increases, tensile strength, elongation, and glass transition temperature of crosslinked polyurethane films increases.…”
Section: Resultsmentioning
confidence: 98%
“…As the degree of microphase separation between hydrophilic and hydrophobic or between soft and hard segments increases, tensile strength, elongation, and glass transition temperature of crosslinked polyurethane films increases. Microphase separation causes an increase of chain entanglement in each segment and therefore microphase separated hydrophilic or hard segments act as physical fillers 14,15,36–38. Figure 6 and 7 represent the stress‐strain curves for UAND and UANH films prepared at the different weight fraction of solvents used during cross‐linking reaction.…”
Section: Resultsmentioning
confidence: 99%
“…It was previously reported that nanophase separation in crosslinked urethane acrylate films strongly influences the mechanical properties of its film 26–33. Unlike macrophase separation, tensile strength, elongation, and glass‐transition temperature of crosslinked polyurethane films increases concomitantly with the degree of nanophase separation between the soft segment and the hard segment.…”
Section: Resultsmentioning
confidence: 99%
“…The length of soft segment and its type is an important parameter to control the dynamic mechanical properties of the polyurethane acrylates (15)(16)(17)(18)(19)(20)(21). Much less work has been devoted to the hard segment type (16,22).…”
Section: Introductionmentioning
confidence: 99%